STRATEGI KADER PARTAI POLITIK DALAM PENDIDIKAN POLITIK BAGI MASYARAKAT DITINJAU DARI PERSPEKTIF KETRAMPILAN KEWARGANEGARAAN (STUDI TERHADAP KADER PARTAI GOLKAR KABUPATEN SRAGEN) - Septiawan, Irawan; ., Winarno; ., Wijianto (Educitizen, 2017)
The aims of the research are to determine: (1) The political education strategies that is applied by Golkar cadres of Sragen in giving political education to Sragen people (2) Whether the political education conducted by Golkar cadres of  Sragen is doing well, in terms of civic skill owned by the society. Based on the result of this research, it can be concluded that (1) Political education strategies which are applied by Golkar cadres as an effort to raise public awareness about politics, consist of: a) a training for Golkar cadres to increase their knowledge about politics; b) teaching political education for society through various activities of Golkar; c) putting the political education through wings party activity and Golkar organization; d) using election campaign agenda for the implementation of political education and Golkar political campaigns; e) teaching political education with personal approach; f) forming the RT stage cadres to teach political education for the society surroundings the cadres. (2) Political education which is applied by Golkar cadres has not been able to establish a good political understanding of the society. The strategies which are applied have not given much help to increase the society political understanding. People who live in Sragen have not fulfilled the citizenship aspect viewed from the civic skill perspective and Sragen society still tend to apply patro-client political culture. The people are still being submissive to the society leaders orders, and  have not been able to improve their own political thinking. This relates to the civic skill that must be ownedby the citizens, which is divided into intelectual skill dan participatory skill.Key terms: Cadres, Political Education, Civic Skill, Political Culture